(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3CNHGQ YHGOd Hf YWjI hfSHg, gh YHGOd Hf YWjI ehdi bQjT ecj, eZf ef GdWHbI GdKGfjI GdJj ajgG jhfS GdcGJH, hSjGW hOMeGf hcGf MSf GdhLg, fXja GdKjGH s
(3BNQgG (B:s
(3haO GHf ejGOI Edi GdefUhQ aeOMg, abGd dg CHhLYaQ deG ONd Edjg(B: (3cja bGd dc GdhdjO? aLYd GdefUhQ jJYLH ced GdSaQ GdChd ef GdLGeY GdcHjQ aj GdEZGfj HMeO Gddg hMSf Yhfg s
(3fSNI QGHYIs
(3HChdgG JQLeI ddeDda hHYOgG agQSJ aj GdSaQ GdChd ef GdcJGHs
(3hQO CjVkG JMJ Qbe (B2176s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs